2022
DOI: 10.1007/s10396-021-01178-z
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonography in undergraduate medical education: a comprehensive review and the education program implemented at Jichi Medical University

Abstract: The concept of point-of-care ultrasound has been widely accepted owing to the development of portable ultrasound systems and growing body of evidence concerning its extensive utility. Thus, it is reasonable to suggest that training to use this modality be included in undergraduate medical education. Training in ultrasonography helps medical students learn basic subjects such as anatomy and physiology, improve their physical examination skills, and acquire diagnostic and procedural skills. Technological advance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0
3

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 148 publications
(195 reference statements)
0
22
0
3
Order By: Relevance
“…This can be attributed to the increased use in all health professions, the observed benefits of early inclusion in anatomy education, a growing anatomy educator shortage, and an increase in new programs to meet the growing physician demand 42,62 . Unfortunately, a lack of education opportunities for additional learning leaves anatomy educators wholly unprepared for the increase in demand 18,63 . To benefit educators and our future healthcare professionals, expanding the availability of continuing education courses that are focused on radiology training is needed to prepare anatomy educators for the challenges that lie ahead.…”
Section: Discussionmentioning
confidence: 99%
“…This can be attributed to the increased use in all health professions, the observed benefits of early inclusion in anatomy education, a growing anatomy educator shortage, and an increase in new programs to meet the growing physician demand 42,62 . Unfortunately, a lack of education opportunities for additional learning leaves anatomy educators wholly unprepared for the increase in demand 18,63 . To benefit educators and our future healthcare professionals, expanding the availability of continuing education courses that are focused on radiology training is needed to prepare anatomy educators for the challenges that lie ahead.…”
Section: Discussionmentioning
confidence: 99%
“…[ 10 , 11 , 12 , 13 ] Studies have also shown that the use of portable or handheld US devices are active learning tools to obtain real-time visual information and that feedback broadens medical students' horizons and increases their motivation to learn. [ 14 , 15 ] In line with this, in the 2020 statement from the Canadian Ultrasound Consensus for Undergraduate Medical Education Group, 85 curricular elements were recommended for inclusion in teaching in Canadian medical school-focused US curricula. [ 16 ]…”
Section: Discussionmentioning
confidence: 99%
“…practice sessions. 19 The use of open practice sessions is also supported by others 24 and may address issues related to restricted curricular time. However, caution must be raised over the potential for the development of bad technique or confusion due to a lack of tutor guidance.…”
Section: Outcome Evaluationmentioning
confidence: 99%